DLC/TI THIN FILMS PROPERTIES PREPARED BY HYBRID LASER TECHNOLOGIES - Jan Mikšovský; Miroslav Jelínek; Petr Písařík; Tomáš Kocourek; Jan Remsa; Karel Jurek (Acta Polytechnica CTU Proceedings)
Layers of diamond-like carbon are usable in many fields of industry as well as in medicine. Many scientific groups have worked with different types of deposition techniques to prepare DLC layers with improved or unique properties. The DLC properties could be improved by various dopations. In this study, we focused on DLC layers doped by titanium, prepared by hybrid laser depositions. Two techniques were used: Dual pulse laser deposition (DualPLD) and pulse laser deposition in combination with magnetron sputtering (PLD/MS). Preliminary tests for morphology, wettability, adhesion, hardness, corrosion, friction and wearability were examined.